Pengaruh Cost dan Expense, Solvabilitas, dan Kapasitas Operasi terhadap Kinerja Operasi - Putri, Silvia Utami; Mulyani, Erly (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to examine the effect of costs and expenses, solvency, and operating capacity on operating performance. This research uses a causative method with a quantitative approach. This research was conducted on infrastructure companies listed on the Indonesia Stock Exchange in 2019-2023 with the sampling method using purposive sampling technique so that 17 sample companies were obtained. The data analysis technique used is multiple linear regression analysis assisted by SPSS software. The results of this study indicate that costs and expenses proxied using operating expenses have a negative effect on operating performance, labor costs and expense costs have a positive effect on operating performance. Solvency proxied using debt to asset ratio has a significant negative effect on operating performance, debt to equity ratio has negative effect on operating performance. Operating capacity proxied using accounts receivable turnover has positive effect on operating performance, and asset turnover has negative effect on operating performance.